2017
DOI: 10.1080/13813455.2017.1401641
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and cardioprotective effects ofUlva lactucaethanolic extract in hypercholesterolemic mice

Abstract: It was established that the green alga, thanks to its bioactive compounds, effectively counteracts cardiotoxic effects of hypercholesterolemic regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Treatment of hypercholesterolemic mice with U. lactuca extract (250 mg/kg body weight) for 4 weeks revealed a cardioprotective effect by improving heart oxidative stress, plasma biochemical parameters, and index of atherogenesis. Additionally, a reduction in gene expression of proinflammatory cytokines (TNFα, IL-1β and IL-6) in the heart of U. lactuca -supplemented animals was also observed [ 225 ]. Kappaphycus alvarezii , a red seaweed, was tested as a food supplement to prevent diet-induced MetS in rats.…”
Section: Bioactive Properties Of Marine Phenolicsmentioning
confidence: 99%
“…Treatment of hypercholesterolemic mice with U. lactuca extract (250 mg/kg body weight) for 4 weeks revealed a cardioprotective effect by improving heart oxidative stress, plasma biochemical parameters, and index of atherogenesis. Additionally, a reduction in gene expression of proinflammatory cytokines (TNFα, IL-1β and IL-6) in the heart of U. lactuca -supplemented animals was also observed [ 225 ]. Kappaphycus alvarezii , a red seaweed, was tested as a food supplement to prevent diet-induced MetS in rats.…”
Section: Bioactive Properties Of Marine Phenolicsmentioning
confidence: 99%
“…Increased reactive oxygen species and inflammation constitute the leading causes of the soaring rates of metabolic diseases such as atherosclerosis and diabetes (Yuan et al, 2019). The search for safe and efficacious approaches to combat continuously expanding oxidative stress, inflammation, and diabetes from natural products has emerged as a crucial strategy because they contain diverse biologically active compounds (Kammoun et al, 2018;Tong et al, 2015). Seaweeds, a promising marine resource, have been exploited and utilized traditionally as food supplements and for various medicinal purposes in Korea, China, Japan, and other Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Ulva lactuca, also known as sea lettuce, is characterized by a high content of carbohydrates, proteins, lipids, fiber, minerals, chlorophyll b, carotenoids, and other nutrients (Kammoun et al, 2018) and is greatly consumed in East Asia. It has good adaptability to different climates, high growth rates, high biomass per acre yield, and negligible requirements for fresh water (Mhatre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulvan extracted from the algae showed cytotoxic activity (Thanh et al, 2016) while the aqueous ethanolic extract showed chemoprotective effect (Delgado-Roche et al, 2019). Ethanolic extract also showed hypolipidemic and cardioprotective effects (Kammoun et al, 2018). Ulva lactuca has a great potential antioxidant activity because it is considered as a potential rich source of natural colorant (El-Baky et al, 2008).…”
Section: Introductionmentioning
confidence: 99%